Evaluation of the apposition in unruptured aneurysms treated with flow diverters by optical coherence tomography: Preliminary clinical experience - Li, Jing; Gong, Wentao; Li, Dongdong; Song, Wenpeng; Fan, Feng; Yuan, Yongjie; Li, Youxiang; Guan, Sheng (Frontiers in Neurology, 2022)
Background The risk of perioperative stroke and the rate of occlusion of long-term aneurysms in the treatment of unruptured aneurysms with flow diverters (FDs) are affected by stent apposition. Optical coherence tomography (OCT) may be an optional technique in evaluating apposition. Purpose To explore the feasibility of OCT imaging technique in evaluating stent apposition in the clinical application of FD for unruptured aneurysms. Methods OCT and Vaso CT were used in patients with indications for surgery to treat unruptured aneurysms with FDs, to evaluate the apposition of FDs after fully released, and to analyze OCT images for FDs apposition and compare with corresponding Vaso CT images. Results A total of 4 patients were enrolled, and OCT found malapposition after FDs placement in all 4 patients, and the maximum gap between the stent and vascular wall ranged from 0.68 mm to 1.95 mm and the length of malapposition ranged from 1.80 mm to 7.40 mm. However, Vaso CT found malapposition only in 2 of the 4 patients ,missed malapposition near aneurysm in all 3 patients treated by FD combined with coiling and could not accurately evaluate the maximum gap and the length of the malapposition. Conclusion: OCT technique is a possible approach to evaluate apposition after the treatment of unruptured aneurysms by FDs.